Early Hunter in the terra firme rainforest: stemmed projectile points from the Curuá goldmines - LIMA, Anderson Marcio Amaral (Programa de Pós-Graduação em Antropologia, 2019)
A pattern of accidental stone-tool finds in the terra firme of the Curua river in the middle Xingu basin suggest a widespread occupation by preceramic hunter-gatherers there, contrary to expectations that the tropical rainforest has insufficient food resources away from the Amazon floodplain. The stone tools include finely flaked stemmed projectile points possibly related to some from terminal Pleistocene contexts at Caverna da Pedra Pintada, Monte Alegre. The food remains with the Monte Alegre tools were from broad-spectrum rupestral and riverine forest foraging. The Xingu points were recovered by artisanal gold-miners in sands and gravels under the Curua river. The miners come across the tools while digging and screening gold-bearing sediments. Those deposits also sometimes contain plant remains and prehistoric wooden artifacts, potential sources of information about ancient habitat, subsistence, and technology. The research team of the Lower Amazon project traveled to several of the underwater find-sites with the miners to prepare for excavations in the future. At one site, Curupite, where miners had found a large stemmed point and a complete palm-wood harpoon foreshaft in 1986, the team used scuba equipment to survey the stream bed and mine pits and map the topography with laser theodolite.